2015
DOI: 10.1016/s1995-7645(14)60316-3
|View full text |Cite
|
Sign up to set email alerts
|

Dengue in pregnancy: an under–reported illness, with special reference to other existing co–infections

Abstract: Establishing diagnosis of dengue infection in pregnancy is important for effective management by the obstetricians particularly the mode of delivery due to the potential risk of hemorrhage for both the mother and the newborn. Co-infections seen in endemic areas may be more common than usually reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 10 publications
3
15
1
1
Order By: Relevance
“…The present study found a high incidence of abortion among women in the first (4/6 women) or second (1/2 women) trimester, and a 41% incidence of preterm birth among women diagnosed at an early stage of the third trimester. Thus, the present results are similar to those of Nidhi et al . Notably, no congenital abnormalities have been reported in any of the studies, even when maternal infection occurs in the first trimester …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The present study found a high incidence of abortion among women in the first (4/6 women) or second (1/2 women) trimester, and a 41% incidence of preterm birth among women diagnosed at an early stage of the third trimester. Thus, the present results are similar to those of Nidhi et al . Notably, no congenital abnormalities have been reported in any of the studies, even when maternal infection occurs in the first trimester …”
Section: Discussionsupporting
confidence: 92%
“…Thus, the present results are similar to those of Nidhi et al . Notably, no congenital abnormalities have been reported in any of the studies, even when maternal infection occurs in the first trimester …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations